Revealing Obstacles: Examining High School Students' Difficulties in Understanding Digestive System Concepts in Class XI MIPA - Anzelina Tristina; Ika Rifqiawati; Mahrawi Mahrawi; Mila Ermila Hendriyani; Rida Oktorida Khastini (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to determine the internal and external factors that cause learning difficulties experienced by class XI students when studying digestive system material. The research used a survey method with a cross-sectional research design involving high school students from three schools in Banten and a class XI biology teacher. Data collection using questionnaires and interviews. Data analysis was carried out using Microsoft Office Excel, and the findings were displayed in the form of a percentage graph. The results of measuring the student learning interest showed that 55.53% of students stated that difficulty in distinguishing types of digestive system enzymes was one of the factors in students' lack of interest in understanding the material. The learning study habits indicators showed that only 28.9% of students applied understanding of the material in their daily lives, this triggered students' lack of memory for the material. Meanwhile, the teacher teaching method indicator showed that 24.43% of students stated that the learning process in class felt monotonous, this was due to the use of learning strategies by teachers which was still relatively lacking, apart from that in the learning facilities indicator, the teaching materials used in schools were still dominant rely on textbooks